Research on logging: cost-benefit analysis of reduced-impact logging in a lowland Dipterocarp forest in Malinau, East Kalimantan - Dwiprabowo, H.; Grulois, S.; Sist, P.; Kartawinata, K. (CIFOR and ITTO, 2002)
This study is a part of the Reduced-Impact Logging (RIL) studies constituting a developmental phase within a long term research strategy in Bulungan research Forest, East Kalimantan. The sylviculture component of the project was to start logging experiments, focusing on the implementation of RIL technique by INHUTANI II in its concession in Malinau, East Kalimantan. Research on the assessment of the immediate and long-term impact of timber harvesting with conventional logging (CL) and RIL techniques in economical terms were carried out to promote the integration of RIL into the current logging techniques at the concession scale. The study was conducted in 1998-1999 on 244 ha block for CL and 138 ha for RIL. This paper mainly presents the immediate financial cost-benefit part of RIL study. Motion study was used to estimate productivity. Hourly productivity on felling and skidding of both techniques were calculated based on felling and skidding time cycles, and unit costs of production were assessed on hourly basis based on the machine cost and piece rate. Unit cost of pre-harvesting operations were assessed on block basis based upon time used by crew to carry out each activity, cost per day, and estimated production per block. Residues of logging were classified and measured on site when the activity was on. Rapid assessment on damage was made by measuring skid tracks caused by CL and RIL.The results showed that hourly productivity of felling and skidding in RIL was 28% and 30% higher than those of CL. Pre-harvesting cost of RIL 60% higher than that of CL. The overall cost of pre-harvesting, felling, skidding and training of RIL was 12% lower than that of CL. Overall residues occurred in the felling and landing site in proportion to respective felled bole volume in RIL was 12% lower that of CL. Proportion of skid tracks to extracted volume (in m2/m3) in RIL was 53% lower than that of CL.